Hall and Joule Heating Impacts on the Rabinowitsch Fluid in a tapered Channel with Permeable Walls - Kareem, Rabiha S.; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2022)
A mathematical model was created to study the influences of Hall current and Joule heating with wall slip conditions on peristaltic motion of Rabinowitsch fluid model through a tapered symmetric channel with Permeable Walls. The governing equations are simplified under low Reynolds number and the long-wavelength approximations. The perturbation method is used to solve the momentum equation. The physiological phenomena are studied for a certain set of pertinent parameters. The effects offered here show that the presence of the hall parameter, coefficient of pseudo-plasticity, and Hartman number impact the flow of the fluid model. Additional, study reveals that a height in the Hall parameter and the velocity slip parameter increases the trapping bolus's apparition. Furthermore, the magnitude of the trapped bolus can be reduced by enhancing the magnetic field.